If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 7) = 6x + 7 Reorder the terms: 6(7 + x) = 6x + 7 (7 * 6 + x * 6) = 6x + 7 (42 + 6x) = 6x + 7 Reorder the terms: 42 + 6x = 7 + 6x Add '-6x' to each side of the equation. 42 + 6x + -6x = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 42 + 0 = 7 + 6x + -6x 42 = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 42 = 7 + 0 42 = 7 Solving 42 = 7 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| ln(x^2+2x)=lnx | | 12+50+1x=18.1 | | 3.50x=5.50x | | 3.50x=5.50 | | 2-(3x+1)=5x-9 | | x+7-(6-x)=10 | | -2m+8m+1=0 | | 3X^2-12X-135=0 | | -(7y+3)-(-6y-7)=-4 | | 1221=16T^2 | | 4t(13t+9)= | | (x-a)m=y | | 3(x+1)=2x-3 | | v^2-44=-8 | | 24=18-16-14 | | .5(4-2a)=a-1.8 | | a^2+6a-13=3 | | a^2+6a-13=0 | | X^2+12X+24= | | 14000+272+x+x=18500 | | (n+3)(6n-1)=0 | | (X-4)-(3-x)=5x+2 | | X-4+3x=8-x | | x^2=-14x-48 | | 2yx=-1 | | T^3-6t^2+12-8=0 | | 15x^2-78x+15=0 | | (s+9)(s-12)=0 | | x+x-14000=18500 | | 14(t-5)+4t=6(3t+4)-11 | | 2senx=-1 | | 8(3x-4)=2(12x+8) |